2007
DOI: 10.1111/j.1744-7348.2007.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and distribution of root‐applied or foliar‐applied 65Zn after flowering in aerobic rice

Abstract: We investigated the uptake and distribution of zinc (Zn) either applied to the roots or to the leaves in rice during grain development. Plants of two aerobic rice cultivars were grown in a nutrient solution with either sufficient Zn or surplus Zn. Root treatment with 1 week's supply of both 65 Zn and unlabelled Zn was started at flowering or 15 days after flowering (DAF). Foliar treatment with 65 Zn applied to the flag leaf or to senescent leaves was carried out at flowering. When 65 Zn was applied to roots, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
3
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 31 publications
4
76
3
4
Order By: Relevance
“…After anthesis stage, both of the rice genotypes continued to uptake the root-supplied Zn with high accumulation occurring in the rice grains (Table 3). This was consistent with the findings of cotton (Constable et al, 1988), red spring wheat (Miller et al, 1994), and aerobic rice (Jiang et al, 2007). Of the total plant Zn, 50% (cotton), 10% (wheat), or 20% (rice) was taken up between anthesis and maturity.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…After anthesis stage, both of the rice genotypes continued to uptake the root-supplied Zn with high accumulation occurring in the rice grains (Table 3). This was consistent with the findings of cotton (Constable et al, 1988), red spring wheat (Miller et al, 1994), and aerobic rice (Jiang et al, 2007). Of the total plant Zn, 50% (cotton), 10% (wheat), or 20% (rice) was taken up between anthesis and maturity.…”
supporting
confidence: 80%
“…Following absorption by the root, Zn is rapidly transported via the xylem to the shoot (Riceman and Jones, 1958). In rice plant, adequate Zn supply leads to a high proportion of Zn located in the shoots (especially stems), while with toxic level of Zn supply (150 µmol/L), a higher proportion of total Zn may accumulate in the roots (Jiang et al, 2007). Zn appears to be most mobile in all micronutrients and its remobilization is closely related to leaf senescence (Marschner, 1995;Uauy et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this wheat study, flag leaf and lower leaves were the major sources of remobilized micronutrients, in contrast to results from rice, where stems accounted for the major source of Zn remobilized to grain [13]. In another rice study, the authors concluded that remobilization accounted for very little grain Zn, and that uptake after anthesis supplied the majority of Zn to grain, with most Zn passing through stems, and only a small amount passing through leaves [25]. It is possible that differences in plant anatomy between rice and wheat [26] account for these contrasting observations, and highlights the importance of conducting similar experiments in a variety of plant species.…”
Section: Remobilization or Continuous Uptake?mentioning
confidence: 41%
“…On the other hand, in rice, xylemtransported Zn from uptake during seed filling might be more important for Zn accumulation in seed than phloem-transported Zn remobilized from leaves (Ziang et al 2007(Ziang et al , 2008. It would seem that contrary to wheat (Zee and O'Brian 1970), there is no xylem discontinuity in the rice plant (Zee 1972;Krishnan and Dayanandan 2003).…”
Section: Iron and Zinc Uptake Accumulation And Translocation To mentioning
confidence: 84%